Multidrug resistance of Staphylococcus epidermidis: An emerging threat to global health - Asmirah Ahmadunissah, Shafiq Aazmi, Umi Marshida Abd Hamid, Aziyah Abdul-Aziz (Journal of Applied Pharmaceutical Science, 2022)
The threat of multidrug resistance in bacteria is a global issue projected to cause 10 million deaths by the year 2050. Staphylococcus epidermidis, which resides on human skin and is generally believed to be harmless, has evolved into a significant opportunistic pathogen. This bacterium has been reported as the etiological agent for various types of infections and its resistance against multiple drugs has challenged the treatment process. The impact is intensified with the possible role of S. epidermidis as a reservoir for antibiotic resistance genes, with the ability to transfer the genes between the various species of staphylococci, including Staphylococcus aureus, potentially creating new strains of multidrug-resistant bacteria. Hence, identifying and acknowledging the potential danger of the underrated S. epidermidis through this review will encourage more global effort to contain the advancement of antimicrobial resistance and subsequently the appropriate therapy for this bacterium.
Keywords: MDR S. epidermidis, mobile genetic element, MRSE, nosocomial pathogen, SCCmec